Knowledge, attitudes and practices of hypertensive patients towards prevention and early detection of chronic kidney disease: a cross sectional study from Palestine - Hala H. Sa'adeh; Razan N. Darwazeh; Amani A. Khalil; Sa'ed H. Zyoud (BMC, 2018)
Abstract Background Hypertension is the second most common cause of chronic kidney disease (CKD). Therefore, the aims of the study were to assess the knowledge, attitudes and practices (KAP) of hypertensive patients towards prevention and early detection of CKD, and to determine the clinical and socio-demographic factors, which affect the KAP regarding prevention of CKD. Methods A cross-sectional study was held using the CKD screening Index to assess the KAP of 374 hypertensive patients who were selected from multiple primary healthcare centers in Nablus, Palestine. The CKD Screening Index is formed of three scales. First, the knowledge scale was a dichotomous scale of 30 items, while the attitude scale used 5-point Likert-type scale for 18 items and finally the practice scale was measured using 4-point Likert-type scale for 12 items. Multiple linear regression analysis was used to determine the association between clinical and socio-demographic factors and practices. Results In total, 374 hypertensive patients participated in the study. The mean age of participants was 59.14 ± 10.4 years, (range 26-85). The median (interquartile range) of the knowledge, attitude, and practice scores of hypertensive patients towards prevention and early detection of CKD were 20 (16-23), 69 (65-72), and 39 (36-42), respectively. In multiple linear regression analysis, patients age < 65 years (p < 0.001) and patients with high education level (p = 0.009) were the only factors significantly associated with higher knowledge scores. Additionally, patients age < 65 years (p = 0.007), patients with high income (p = 0.005), and patients with high knowledge score (p < 0.001) were the only factors significantly associated with higher attitude scores. Furthermore, regression analysis showed that patients with higher total knowledge (p = 0.001) as well as higher total attitudes scores towards CKD prevention (p < 0.001), male gender (p = 0.048), and patients with normal body mass index (BMI) (p = 0.026) were statistically significantly associated with higher practice score towards CKD prevention. Conclusions Among hypertensive patients, higher scores for total knowledge and attitudes toward prevention, male sex, and normal BMI were associated with modestly higher scores for prevention practices. Finally the findings may encourage healthcare workers to give better counseling to improve knowledge.